2018
DOI: 10.26656/fr.2017.2(6).109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different drying treatments on concentration of curcumin in raw Curcuma longa L.

Abstract: Curcuma longa L., commonly known as turmeric, is a member of the ginger family (Zingiberaceae), native to Southwest India. Curcumin is the active ingredient of the turmeric. In traditional Indian medicine, turmeric has been used to treat stomach and liver ailments, as well as topically to heal sores, for its supposed antimicrobial property. The curcumin is believed to have a wide range of biological effects including antiinflammatory, antioxidant, antitumor, antibacterial, and antiviral activities, which indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
3
15
0
1
Order By: Relevance
“…A negative impact of shade drying (GSD) than STD on curcumin concentration was also reported previously [33]. The GSD took 16 days, followed by OSD, and the color of GSD dried samples appeared dull due to a lower rate of moisture loss with a natural convection.…”
Section: Curcuminsupporting
confidence: 69%
“…A negative impact of shade drying (GSD) than STD on curcumin concentration was also reported previously [33]. The GSD took 16 days, followed by OSD, and the color of GSD dried samples appeared dull due to a lower rate of moisture loss with a natural convection.…”
Section: Curcuminsupporting
confidence: 69%
“…Solar drying was also widely used for drying turmeric, but it has several disadvantages, such as more drying time during insufficient sunlight, laborious process, and the chances of contamination, and infestation is more (Borah et al, 2017). Several researchers (Fudholi, Ariffin, Ruslan, Othman, & Sopian, 2012; Lokhande, Kale, Sahoo, & Ranveer, 2013; Gan, Charters, Driscoll, & Srzednicki, 2017; Raza, Ali, Yusof, Nasir, & Muneer, 2018) had been conducted studies in hot air dryers, but the major drawbacks are more consumption of energy and drying time in falling rate period, which makes the product harder (Raza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin in turmeric rhizomes is reduced by direct and indirect solar radiation. Raza et al [ 27 ] reported lower curcumin contents of dried rhizomes from sun drying and solar tunnel drying than that from shade drying. Mahayothee et al [ 28 ] also reported that drying in a solar greenhouse dryer covered with a polycarbonate sheet reduced curcumin contents in cassumunar ginger.…”
Section: Introductionmentioning
confidence: 99%